2015
DOI: 10.1002/cam4.401
|View full text |Cite
|
Sign up to set email alerts
|

Cyr61 promotes CD204 expression and the migration of macrophages via MEK/ERK pathway in esophageal squamous cell carcinoma

Abstract: Tumor-associated macrophages (TAMs) are known to be involved in the progression of various human malignancies. We previously demonstrated that CD204 was a useful marker for TAMs contributing to the angiogenesis, progression, and prognosis of human esophageal squamous cell carcinoma (ESCC). We also showed that conditioned media of ESCC cell lines induced CD204 expression in THP-1 human monocytic leukemia cells. Here, we performed a cDNA microarray analysis between THP-1 cells stimulated with TPA (macrophage [MΦ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 43 publications
0
33
0
Order By: Relevance
“…Neither murine PBMCs nor endothelial cells released CCN1 on a short-term basis, although endothelial cell-derived CCN1 coats the surface of these cells in the steady state and 18-h treatment with TNF-α and bafilomycin A1 stimulated CCN1 release by human PBMCs (18). These results are in accordance with the chemoattractant properties of CCN1 for monocytes/macrophages in the early phase of inflammation, whereas PBMC-derived CCN1 locally immobilize recruited leukocytes in the invaded tissue after extravasation at later time points (18,19,(50)(51)(52)(53).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Neither murine PBMCs nor endothelial cells released CCN1 on a short-term basis, although endothelial cell-derived CCN1 coats the surface of these cells in the steady state and 18-h treatment with TNF-α and bafilomycin A1 stimulated CCN1 release by human PBMCs (18). These results are in accordance with the chemoattractant properties of CCN1 for monocytes/macrophages in the early phase of inflammation, whereas PBMC-derived CCN1 locally immobilize recruited leukocytes in the invaded tissue after extravasation at later time points (18,19,(50)(51)(52)(53).…”
Section: Discussionmentioning
confidence: 58%
“…Interestingly, increased soluble CCN1 levels are observed in synovial fluid from rheumatoid arthritis patients (15) and in the serum of SLE patients (64). Hence, the chemoattractant properties of CCN1 for human and murine monocytes and macrophages (15,16,18,19) strongly implicates CCN1 in the numerous pathologies in which TLR7 activity plays an important role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the matricellular protein cysteine-rich angiogenic inducer 61, which is enriched in tissues of esophageal squamous cell carcinoma, is believed to induce CD204 expression in infiltrated macrophages. 144 The molecular functions of CD163 and CD204 themselves are also suggested directly influence the function of M2-TAMs. CD163 is a membrane protein belonging to the scavenger receptor cysteine-rich domain family and acts as an endocytic receptor for a hemoglobin-haptoglobin (Hb-Hp) complex.…”
Section: Poor Prognosismentioning
confidence: 99%
“…Therefore, it is a formidable task to study and explore novel biomarkers or therapeutic targets for ESCC patients. Recently some research findings have indicated that the initiation and development of ESCC involved the mutation of numerous oncogenes and anti-oncogenes, and thus were characterized by the synergetic effect of multiple genes, factors and steps (5,6), yet more effort is still needed to study the genetic and molecular changes underlying the development of ESCC.…”
Section: Introductionmentioning
confidence: 99%